Hubungan Antara Personal Hygiene Dengan Kejadian Kusta - Tasalina Yohana Parameswari Gustam (Universitas Pahlawan Tuanku Tambusai, 2023)
Leprosy in East Java account for 24% of leprosy in Indonesia. There are several risk factors that affect the incidence of leprosy, one of which is personal hygiene. This study aims to determine the relationship between personal hygiene and the incidence of leprosy. Type of analytical observational research with case control matching research design to determine the relationship between personal hygiene and the incidence of leprosy in residents living in Kenjeran, Semampir, and Tandes sub-districts. This study was conducted between January-April 2017. The number of case respondents was 28 people and controls were 28 people. Data collection by interviews and medical record tracing. Bivariate analysis was performed using SPSS 16. The results obtained P value > 0.05 showed that there was no relationship between personal hygiene and the incidence of leprosy. The conclusion of this study is that there is no relationship between personal hygiene and the incidence of leprosy in Kenjeran, Tandes, and Semampir sub-districts. Keywords: Leprosy, personal hygiene, risk factor